A test-cell installation of a gas turbine engine to investigate the performance advantages of low aromatic fuel - Bester, Nigel (Department of Mechanical Engineering, 2015)
The foreseeable opportunity for LTFT jet fuel has spurred an initiative for Sasol Technology Fuels Research to increase the level of gas turbine expertise within the mechanical group. This included gaining an intimate familiarity with the jet fuel business, and all relevant aspects of gas turbine technology and jet fuel combustion performance. This project formed a component of the research activity.ObjectivesThe primary focus of the project was to ascertain the extent to which reducing aromatic content would a ect the performance of a gas turbine. However, since no facilities existed at the Sasol Advanced Fuels Laboratory (SAFL) for jet fuels research, the rst objective was to establish a working test cell with which to complete the research. Once operational, the engine was instrumented to study the thermal loading on the combustor, and a database of soot emissions measurements was populated while operating on a matrix of fuels.Experimental SetupA T63-A-700, Model 250-C18 B gas turbine was installed in a test cell at the Sasol Advanced Fuels Laboratory. The engine was instrumented to determine the performance implications of jet fuels with varying aromatic contents. Synthetic Para nic Kerosene (SPK) containing zero aromatics, and a petroleum{derived Jet A-1 fuel containing 19.0 % aromatics were the two test fuels incorporated to determine the e ect of aromatics on engine performance. Liner temperature measurements were attained via an instrumented combustor liner, as well as exhaust gas sampling employed to determine engine soot emissions.Discussion of ResultsThe results showed a mean improvement in engine e ciency of 1.17% when operating at cruise conditions on SPK versus petroleum{dervied Jet A-1. The e ciency was attained via four means; an improvement in the thermodynamic properties of the combustion products, an increase in combustione ciency, a reduction in the viscosity of the combustion products and a reduction in the liner pressure loss, also linked to viscous e ectsThere was an 86.8% reduction in soot emissions at cruise conditions, and a 95.3% reduction in soot emissions at idle conditions with operation on SPK versus petroleum{derived Jet A-1. The reduction in soot was attributed to the reduction in aromatic content of the fuel. There was a consistent reduction in liner operating temperature at cruise conditions measured with operation on SPK. The liner temperature reduced by 20 C in the vicinity of the primary combustion zone, and about 5 C at the turbine end of the combustor liner. The reduction in operating temperature was primarily attributed to the reduction in soot, and the resultant reduction in thermal radiation heat transfer.ConclusionsThe soot formation tendency of aromatics were seen during experimentation, with an 86.8% and 95.3% reduction in soot formation measured during operation on aromatic free SPK versus a petroleum{derived Jet A-1. The reduction in soot within the combustor resulted in a large reduction in the thermal radiation heat transfer to the combustor liner, and caused a lower combustor liner operating temperature to result. The greater H/C ratio of SPK with respect to petroleum{derived Jet A-1 caused the thermodynamic properties of the combustion products to change directionally toward improving energy extraction via a turbine. The H/C ratio e ect was due to the reduction of aromatic molecules in the fuel, and the inclusion of more para nic molecule with a greater H/C ratio.